Hubungan Kepemimpinan dan Komunikasi dengan Kinerja Tenaga Kesehatan di Seluruh Puskesmas Kota Yogyakarta - Maya Amalia (International Journal of Healthcare Research, 2019)
One of the government's efforts to achieve health development goals is the issuance of the Minister of Health regulation of the Republic of Indonesia Number 75 year 2014 about Community Health Center (Puskesmas).Good leadership and communication are needed for the achievement of organizational goals. Implementation of community health center policies that are less than optimal can be characterized by lack of communication, programs that haven't been socialized and weak human resources in providing services. This can occur because the employees not fulfill their duties and responsibilities. So evaluation is needed to produce good performance. The purpose of this study is to find out the relationship between leadership and communication with the performance of health workers in all over the community health centers in Yogyakarta City. This research is analytic research with cross-sectional approach. There are 189 community health centers employees as the samples of this study who were selected by propotionate stratified random sampling. This study conducted in April - June 2019 in all over community health center in Yogyakarta city. The data were analyzed using univariate and bivariate analysis with chi square statistical test. The chi square statistical test show that the p-value of leadership with performance is 0,012 (p-value <0,05), as well as the statistical test performed on communication variables with performance show that the p-value is 0,011 (p-value <0,05). There is a significant relationship between leadership and communication with performance.